PENGARUH PENGGUNAAN SHOPEE PAYLATER TERHADAP PERILAKU KONSUMTIF (STUDI MAHASISWA JAKARTA) - Maryani, Dina; Maya, Siska (Journal of Fundamental Management (JFM), 2024)
This research aims to determine the effect of using Shopee PayLater on consumer behavior (Jakarta student study). The data collection methods used are primary and secondary data sources. The sampling technique was carried out using a non-probability sampling technique with purposive sampling from a population of 5,104 and a sample of 100 respondents. This research uses 2 (two) variables, namely: Use of Shopee Paylater  and Consumptive Behavior. The research design or method used is a quantitative method with a Likert scale measuring instrument. The data analysis technique uses a simple linear regression test and correlation coefficient with Microsoft Excel. Test the hypothesis using the t test. the shopee paylater variable  has a significant effect on the consumer behavior variable  in the Jakarta student study. The magnitude of this influence was 42%, while 58% of the influence was caused by other factors not examined in this study. This means that the accepted hypothesis is H1, namely that the use of shopee paylater  influences the consumptive behavior  of the Jakarta student study.